Security for the digital world within an ethical framework (Digital enlightenment series ;, 2016)
The Digital Enlightenment Forum (DigEnlight) takes the view that the new regulatory and legal safeguards required for our digital world must be developed within a framework that incorporates what they call 'digital ethics'.